Psychometric Properties of the Reconstructed Hamilton Depression and Anxiety Scales. Issue 8 (August 2017) - Porter, Eliora; Chambless, Dianne L.; McCarthy, Kevin S.; DeRubeis, Robert J.; Sharpless, Brian A.; Barrett, Marna S.; Milrod, Barbara; Hollon, Steven D.; Barber, Jacques P.
Abstract : Abstract: Although widely used, the Hamilton Rating Scale for Depression (HRSD) and Hamilton Anxiety Rating Scale (HARS) discriminate poorly between depression and anxiety. To address this problem, Riskind, Beck, Brown, and Steer ( J Nerv Ment Dis . 175:474–479, 1987) created the Reconstructed Hamilton Scales by reconfiguring HRSD and HARS items into modified scales. To further analyze the reconstructed scales, we examined their factor structure and criterion-related validity in a sample of patients with major depressive disorder and no comorbid anxiety disorders ( n = 215) or with panic disorder and no comorbid mood disorders ( n = 149). Factor analysis results were largely consistent with those of Riskind et al. The correlation between the new reconstructed scales was small. Compared with the original scales, the new reconstructed scales correlated more strongly with diagnosis in the expected direction. The findings recommend the use of the reconstructed HRSD over the original HRSD but highlight problems with the criterion-related validity of the original and reconstructed HARS.